A prevalence study of restless legs syndrome in Turkish children and adolescents - TÜRKDOĞAN, DİLŞAD; BEKİROĞLU, GÜLNAZ NURAL; ZAİMOĞLU, SENNUR (ELSEVIER, 2011)
Objective: To determine the prevalence of restless legs syndrome (RLS) in Turkish school children and adolescents during the past 12 months. Methods: A cross-sectional population study conducted in three primary and four high schools was randomly selected in the Umraniye district of Istanbul. In the first step, a 7-item questionnaire including pediatric diagnostic criteria of RLS proposed by the International Restless Legs Study Group was given to 4346 students aged from 10 to 19 years in the classroom. Candidates for definite RLS or probable RLS were selected by a face-to-face interview done by an expert. In the second step, a 58-item questionnaire was administered to the families of the selected subjects. The questionnaire aimed to survey family history, parent's awareness, and their behaviors for seeking treatment, as well as the differential diagnosis and comorbid disorders of RLS. Results: Definite RLS was diagnosed in 119 (2.74%) of the subjects and was more prevalent in females (3.42%) compared to males (2.04%) (p = 0.007). A family history of RLS was positive in 15.8% of the first-degree relatives of those 119 subjects. Less than half of the parents (45%) were aware of their children's symptoms and only 10.9% of these parents consulted medical centers. The most prevalent symptoms of sleep disturbances were restless sleep (28.6%) and daytime sleepiness (21%). Growing pains were reported in 54.5% of the 119 subjects with definite RLS. Symptoms of Attention-Deficit/Hyperactivity Disorder were found in 15.3% of the 119 subjects. Conclusions: RLS is prevalent in Turkish children and adolescents although family awareness of RLS is relatively low. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Restless legs syndrome; Children and adolescents; Prevalence; Comorbid disorders; Attention-deficit/hyperactivity disorder; Growing pain; TELEPHONE DIAGNOSTIC INTERVIEW; PRIMARY-CARE; SYNDROME RLS; SYNDROME SYMPTOMS; SLEEP DISORDERS; GROWING PAINS; CHILDHOOD; HYPERACTIVITY; EPIDEMIOLOGY; POPULATION